2017
DOI: 10.3791/55047
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Culture of Myogenic Precursor Cells/Primary Myoblasts from Skeletal Muscle of Adult and Aged Humans

Abstract: Skeletal muscle homeostasis depends on muscle growth (hypertrophy), atrophy and regeneration. During ageing and in several diseases, muscle wasting occurs. Loss of muscle mass and function is associated with muscle fiber type atrophy, fiber type switching, defective muscle regeneration associated with dysfunction of satellite cells, muscle stem cells, and other pathophysiological processes. These changes are associated with changes in intracellular as well as local and systemic niches. In addition to most comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…S2B) (Ocalan et al, 1988). In addition, recent studies showed that laminin promotes proliferation of human myoblasts (Chowdhury et al, 2015; Soriano-Arroquia et al, 2017) and maintains their myogenic phenotype over long-term culture (Penton et al, 2016), suggesting that this isolation protocol may also be applicable to human skeletal muscle myoblasts. The high serum medium supplemented with CEE and bFGF facilitated the migration and expansion of myoblasts on matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…S2B) (Ocalan et al, 1988). In addition, recent studies showed that laminin promotes proliferation of human myoblasts (Chowdhury et al, 2015; Soriano-Arroquia et al, 2017) and maintains their myogenic phenotype over long-term culture (Penton et al, 2016), suggesting that this isolation protocol may also be applicable to human skeletal muscle myoblasts. The high serum medium supplemented with CEE and bFGF facilitated the migration and expansion of myoblasts on matrigel.…”
Section: Discussionmentioning
confidence: 99%
“…Primary myoblasts from adult (6 months old) and old (24 months old) mice were prepared from EDL muscles following single fibre isolation as previously described [12,39]. Briefly, EDL muscle from both legs was digested with 1.5 U/mL collagenase D, 2.4 U/mL dispase II and 2.5 mM CaCl 2 .…”
Section: Isolation Of Primary Myoblasts From Mouse Skeletal Musclementioning
confidence: 99%
“…Digested muscle was filtered and spun to remove undigested tissue and plated on surfaces covered with 10 µg/mL laminin and incubated with DMEM media with 20% FBS, 10% horse serum, 1% l-glutamine and 1% penicillin/streptomycin at 37 • C and 5% CO 2 . Primary myoblasts were grown in DMEM media supplemented with 10% FBS, 1% l-glutamine and 1% penicillin/streptomycin [39].…”
Section: Isolation Of Primary Myoblasts From Mouse Skeletal Musclementioning
confidence: 99%
See 1 more Smart Citation
“…At the neuromuscular synapse, the DAPC is also formed with utrophin, also a 427 kDa protein, instead of dystrophin. The phosphorylation of α-DB1 through NRG/ERBB signaling stabilized acetylcholine receptors (AChRs) at the neuromuscular synapse 1,2 . Duchenne and Becker muscular dystrophy (D/BMD) patients have mutation(s) in the dystrophin gene, resulting in the expression of a truncated dystrophin protein [3][4][5][6] . The main body of research on DMD argues for the lack of dystrophin in skeletal muscle as the cause for DMD.…”
Section: Introductionmentioning
confidence: 99%